Pembelajaran Berdiferensiasi Perspektif Al-Qur'an Surah Al-Hujurat Ayat 13 - Fakhriah, Nyimas; Razzaq, Abdur; Imron, Kristina (Muróbbî: Jurnal Ilmu Pendidikan, 2025)
This research is qualitative in approach with a research method in the form of a literature study or library research that examines literature reviews related to differentiated learning and Q.S. Al-Hujurat verse 13. The data collected is based on the Qur'an as well as journals and related books as supporting data. The result of this research is the relationship between Q.S. Al-Hujurat verse 13 and differentiated learning is the similarity of views on the value of tolerance and justice. Differentiated learning tries to make differences in students' learning styles and interests as a unifying tool so as to achieve learning goals that prioritize student learning needs. Differentiated learning and Q.S. Al-Hujurat verse 13 both uphold equal rights to the diversity created by Allah Swt. All students must have their learning needs met fairly and equally so that they can achieve maximum.